Classics: A very short instroduction - Beard, Mary; Henderson, John (Oxford Oxford university press, 1995)
This Very Short Introduction to Classics links a haunting temple on a lonely mountainside to the glory of ancient Greece and the grandeur of Rome, and to Classics within modern culture-from Jefferson and Byron to Asterix and Ben-Hur. We are all Classicists - we come into touch with the Classics daily: in our culture, politics, medicine, architecture, language, and literature. What are the true roots of these influences, however, and how do our interpretations of these aspects of the Classics differ from their original reception? This introduction to the Classics begins with a visit to the British Museum to view the frieze which once decorated the Apollo Temple at Bassae. Through these sculptures, John Henderson and Mary Beard prompt us to consider the significance of Classics as a means of discovery and enquiry, its value in terms of literature, philposophy, and culture, and its importance as a source of imagery.